Blue Ribbon Panel Consensus Report on Better Practices of Personal Information Management - Teevan, Jaime (2015)
Researchers have been studying personal information management (PIM) for many years, but little exists by way of practical advice for how individuals might better manage their own information. The work reported here employed the Delphi Method to engage PIM researchers in a five-round extended dialog concerning practices of PIM. Participants identified key everyday choices of PIM, suggested alternatives for each and identified pros and cons of each alternative as a practice of PIM. The results that emerged from this process are summarized along four dimensions: 1) Information capture and retention for later use, 2) Finding and organizing information across applications, 3) Reminding and managing attention, tasks, and to-dos, and 4) Managing versions, controlling clutter, and combatting fragmentation.